The Effect of formative assessment on reading comprehension - Fatih Çetin Çetinkaya; Muhammet Sönmez (International Journal of Assessment Tools in Education, 2022)
The aim of this research is to set forth the effects of formative assessment methods on reading comprehension. To this end, reading status of a group of students was assessed with formative assessment methods, while that of another group was evaluated with traditional ones. The research was carried out by using unequalised quasi-experimental design. The experimental and control groups of the research were randomly assigned. The study group consisted of 50 3rd grade students of a primary school in the Dilovası district of Kocaeli city, Türkiye. The data of the study were obtained from the texts within 3rd grade curriculum and from the comprehension questions prepared for these texts. The data were analyzed via SPSS 22 program. Mann-Whitney and Wilcoxon signed rank tests were used during analyses. In the findings of the research, a highly significant difference was observed in favor of the experimental group. As a result of the findings of the research, it was observed that formative assessment methods contributed to reading comprehension success positively.